Advantages of single step over step-by-step screening for sleep disorders. Issue 4 (4th July 2018) - Tonetti, Lorenzo; Filardi, Marco; Plazzi, Giuseppe; Natale, Vincenzo
Abstract: Two secondary analyses of previously collected data were carried out to detect the best screening strategy for primary insomnia (Study 1) and narcolepsy type 1 (Study 2) between two different approaches: (A) step-by-step (i.e. first step: subjective assessment through mini sleep questionnaire – MSQ; second step: objective assessment through actigraphic assessment only for those positive at the first step) and (B) single step (i.e. simultaneous subjective and objective assessment). Forty-six healthy controls (HC) and 46 primary insomnia patients (PI) were analyzed in Study 1; 40 HC and 40 narcolepsy type-1 patients (NT1) were analyzed in Study 2. All participants originally wore the Micro Motionlogger Watch actigraph (Ambulatory Monitoring, Inc., Ardlsey, NY) around the non-dominant wrist for seven consecutive days, and upon completing the actigraphic assessment filled in the MSQ. In Study 1, the single-step approach correctly identified 93.48% of PI, while only 50% of PI were correctly identified by the step-by-step approach. In Study 2, 100% of NT1 was correctly classified through the single-step approach, while 72.5% according to the step-by-step approach. The result of both studies highlights the higher appropriateness of single step (i.e. bi-dimensional assessment) compared to step-by-step approach to screen primary insomnia and narcolepsy type-1 patients.